1987
DOI: 10.1051/rnd:19870403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypothalamic hormones (GRF, TRH, Somatostatin) and insulin-like growth factor I on growth hormone secretion from prepubertal male lamb pituitary cultures

Abstract: Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In all of the species cited above, including lambs, the maximal effective dose of GRF is 0.5-1 gg/kg. Similarities among species concerning GRF dose-response effect have been confirmed in pituitary cell cultures (Law et al, 1984 ;Blanchard et al, 1987 ;Brazeau et al, 1982).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…In all of the species cited above, including lambs, the maximal effective dose of GRF is 0.5-1 gg/kg. Similarities among species concerning GRF dose-response effect have been confirmed in pituitary cell cultures (Law et al, 1984 ;Blanchard et al, 1987 ;Brazeau et al, 1982).…”
mentioning
confidence: 60%
“…In sheep, hGRF has been shown to stimulate GH secretion in the fetus (Ohmura et al, 1984), as well as in cultured pituitary cells (Law et al, 1984 ;Blanchard et al, 1987). Therefore hGRF appears to be an appropriate form of the peptide to use to investigate dynamic changes of GH release in sheep.…”
mentioning
confidence: 99%
“…The GRF-induced GH secretion was also decreased by IGF-I, but this reduction was less than that seen for basal secretion. In rodents (Berelowitz et al l98l) and sheep (Blanchard et al 1987;Silverman et al 1989), IGF-I caused a significant reduction in GRF-induced GH secretion, indicating that IGF-I may control GH secretion by modulating GRF effects at the pituitary level. In contrast with our results, Blanchard et al (1988) Glenn (1996), who showed that IGF-I did not suppress basal or GRFstimulated GH release in bovine pituitarv cells.…”
Section: Resultsmentioning
confidence: 99%
“…Pituitary Gi{ secre-and hypothalamic (Berelowitz 1981;Brazeau et al' 1982) iion is under the control of nvo hypothalamic faciors, n'amely, levels in rats. Such results at the pituitary lgvel yele^l-1o found GRF (Guillemin et al 1982f 'and somatostarin (SRIF; with in vitro studies in lambs (Blanchard et al 1987) and in Brazeau et al 1973). The GRF-induced GH response in fetal vivo studies in rats (Thnnenbaum et al' 1983).…”
mentioning
confidence: 89%
“…TRH seems to be equipotent to GHRH 109 in the case of chickens 110 but not in fowl 110–113 . In mammals, TRH has been demonstrated to stimulate GH release in cattle 114 and in sheep 73,115,116 . In humans, the ability of TRH to induce GH release is maintained in tumor somatotropinoma cells, while this effect is less evident in normal subjects, thereby suggesting that, as for PACAP, TRH has lost, at least in part, its capacity to act as a primary stimulus for the somatotrope axis 117–120 …”
Section: Regulation Of Gh Secretionmentioning
confidence: 99%